Methodological guidelines for practical works completion from the academic discipline "Fundamentals of Scientific Research" - Plaksiy, Yu. A. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The most important component of any scientific research is an experiment - a method of empirical research, which is based on the researcher's purposeful intervention in the process of scientific knowledge of the phenomenon of reality by creating controlled and managed conditions that allow to highlight certain qualities and relationships in the object of research and reproduce them repeatedly. Each experiment ends with a transition from empirical study to processing of the obtained experimental data, logical generalizations, analysis and theoretical interpretation of the obtained factual material. An important section of the methodology for conducting an experiment is the choice of methods for processing and analyzing experimental data. The results of experiments should be reduced to such forms of recording as tables, graphs, formulas, nomograms, which allow to quickly and qualitatively interpret the obtained results. Particular attention in the experimental methodology should be paid to mathematical methods of processing and analyzing the obtained experimental data - establishing empirical dependencies, approximating relationships between varying characteristics, establishing criteria, etc. The purpose of practical works in the academic discipline "Fundamentals of Scientific Research" is to study methods for processing experimental data, to build regression models of the processes under study on their basis, and to apply methods for analyzing the obtained models. Procedure for performing practical works. Before starting practical work, it is necessary to: 1) receive a task for practical work from the teacher; 2) familiarize yourself with the necessary theoretical material for performing practical work; 2) familiarize yourself with the algorithm of the method and draw up a flowchart of the algorithm; 3) draw up a computer program for implementing the algorithm on a PC and perform the necessary calculations; 4) present the results of the work in an appropriate form; 5) draw conclusions based on the results of the work. Requirements for presenting the results of practical works. Based on the results of practical works, a single report must be drawn up in electronic form, which includes a title page, a problem statement with initial data, a flowchart of the algorithms used in the report, a tabular and graphical presentation of the obtained calculation results, and conclusions regarding the interpretation of the obtained results.
Keywords: methodological guidelines; practical works; fundamentals of scientific research; experimental data; mathematical models; squares method